Writing for the workplace : business communication for professionals - Mizrahi, Janet. (Corporate communication collection., 2015)
Employers consider communication one of the most critical skills for workers today. Writing for the Workplace: Business Communication for Professionals is an easy-to-follow guide that provides strategies for effective professional communication. Written to address the needs of both students entering the workforce and business professionals looking to improve their written communication, the book offers guides to compose typical workplace documents, from effective e-mails and convincing reports to winning presentations and engaging resumes. This concise book offers busy readers concrete strategies to improve their workplace writing. Part I addresses writing in today's fast-paced business and professional contexts and discusses writing as a process, professional writing style, writing tools, characteristics of effective workplace communication, and basic document design. Part II is a more detailed exploration of common written genres in the workplace and discusses correspondence such as e-mail messages, letters, memos, and social media for specific workplace situations. Part III delves into short and long reports and business presentations, and Part IV is dedicated to employment communication. Each section includes many sample documents and examines organization, tone, and genre elements. A list of common writing errors to avoid, helpful checklists, and easily scannable text make the book accessible and readable.